Optimization of staggered array configurations to enhance the aerodynamic performance of Darrieus wind turbines - Yosua Heru Irawan; Aditya Sukma Nugraha; Po Ting Lin (University of Muhammadiyah Malang, 2024)
This research focuses on optimizing the arrangement of Darrieus wind turbines through an adjustable R array, which represents the spacing between the turbine rotors. The ANSYS Fluent solver, employing the k-epsilon turbulent model and sliding mesh technique, is utilized to predict turbine performance. Additionally, a grid independence test is conducted to validate the solver's effectiveness. The optimization of the R array is achieved using the conjugate gradient method. Simulation results indicate that a blade grid size of 1 mm results in an error under 1%. A smaller R array yields a lower average coefficient of power (Cpaverage) due to the wake interactions between the rotors. The optimal spacing for each turbine to achieve a Cpaverage value of 0.4088 is determined to be 1.772 meters.